Compósito reforçado com sisal para aplicação na moda - Oliveira, José Orlando de (2012)
The objective of this research is the fabrication of a composite reinforced with dyed sisal fiber and polyester matrix for application in the fields such as, fashion, clothing, interior textiles; fashion accessories are some of the examples. For the fabrication of the composite, the sisal fibers were subjected to processes such as: chemical treatment with sodium hydroxide (NaOH) in the removal of impurities; bleaching for removing the yellowish color of the natural fiber and dyeing with direct dyes to confer the colors blue, green and orange. The search for new technologies ecologically correct has become a major concern in recent decades. Studies show that composite polymer reinforced by natural fibers is suitable for a large number of applications, and its use is advantageous in terms of economic and ecological. The dyed fibers were cut to a length of 30 mm, is used in the confection of webs. For this purpose, a web preparer by immersion, developed in the Laboratory of Chemical Textile of UFRN. The composite sheets measuring 300 x 300 x3 mm were molded by compression, with unsaturated orthophthalic polyester as matrix, and the samples in sizes 150 x 25 x 3 mm were cut with the aid of a laser machine, to be subjected to traction and flexion. The mechanical properties of traction and flexion in three points were performed in the Laboratory of metal and mechanical tests of Materials Engineering of UFRN. The resulting samples from the tests were evaluated in scanning electron microscope (SEM) at CTGas RN. On the basis of the analysis of the results from the mechanical tests, it was observed that the composite had good mechanical behavior, both in traction as in flexion. Furthermore, it was observed that in the water absorption test, the samples had a different percentage among themselves, this occurred due to the variation of density found in the fibre webs. The images of the SEM showed the failures from the manufacturing process and the adhesion of fibre/matrix. When the samples were prepared with the dyed fibers to be applied in fashion, the results were positive, and it can be concluded that the main objective of this work was achieved